An Assessment of Vehicle Transport-Induced Air Pollution along a Traffic Corridor in Lagos - Ege, Emmanuel; Adelugba, AO; Adedeji, Wasiu Oyediran; Oni, Samuel Iyiola; Oke, Sunday Ayoola; Asenime, Charles (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Air pollution control is receiving more attention for policy support, however, in Lagos, Nigeria, this phenomenon is not being used to its fullest. Furthermore, the use of experimental data from localized field studies is dismally low, causing poor policy decisions. This work is a new initiative to collect and analyze transport-stimulated air pollution in three areas of Lagos: Iyana Ipaja, Egbeda, and Ikotun using a concentration of pollutants (CO, SO2, and NO2) and emission severities. At Iyana Ipaja, CO was above the safe limit stipulated by the Federal Environmental Protection Agency (FEPA) and SO2 and NO2 were below the safe limit. At Egbeda, NO2 and SO2 varied between 0.35-0.4 and 0.2-0.3 parts per million (ppm) with the highest value recorded during the PM peak while CO exceeded the maximum daily limit of 10 ppm. At Ikotun, the CO was 105.8ppm, which is above the stipulated value of 10ppm and SO2 was below the value stipulated by FEPA while NO2 varied between 0.15ppm and 0.45ppm, which is lower than the safe limit of 0.06 parts per million (ppm). Static and dynamic emission levels ( and ) for CO were most severe for Egbeda at (14.18 and 10.43 ppm/m), respectively. For SO2, ( and ) were most severe for Iyana Ipaja at (0.08 and 1.00 ppm/m), respectively. The ( and ) for Iyana Ipaja and Ikotun were tied at (0.08 and 1.00 ppm/m), respectively. The novelty of this work is the proposal of a robust dataset and analysis on the concentration of certain pollutants (CO, SO2 and NO2) and emission seventies in Lagos, which serves as a cornerstone approach to developing and implementing transportation and environmental policy in Lagos. Results suggest that the obtained method and data values adequately represent the air pollution values for policy decision usage.